Designing the world's best children's hospitals 3 the future of healing environments - Komiske, Bruce King.; National Association of Children's Hospitals and Related Institutions (Mulgrave, Vic. Images Pub., 2012)
Following the success of 'Designing the World's Best Children's Hospitals' 1 and 2, this new publication provides an up-to-date reference guide for healthcare teams, design professionals and community members, who together engage in the exciting process of creating new healing environments for children's hospitals or paediatric units.
"In cooperation with, the National Association of Children's Hospitals and Related Institutions, the Children's Hospital Association, FKP Architects, HDR, HKS Architects, KMD Architects, Stantec, and ZGF Architects LLP."
Keywords: Children -- Hospitals -- Design and construction -- Pictorial works; Children -- Hospitals -- United States -- Pictorial works; Hospital architecture -- United States -- Pictorial works; Hospital buildings -- Design and construction -- Pictorial works